Perception of Visual Impairment Towards the Aesthetic of Architectural Elements - Sari, Komang Ayu Laksmi Harshinta; Hayati, Arina; Samodra, FX Teddy Badai (Institut Teknologi Sepuluh Nopember, 2020)
Phenomenology in architecture is associated with perception between the subject and the space, which one of the studies includes multisensory experience. In general, contemporary architecture accentuates the visual experience, among other sensory modalities. Therefore, it is necessary to conduct research about the exploration of multisensory perception in architectural design. This study aims to explore how sensory activities or blind and visual impaired experience the spatial and the elements of architecture. This study is started by examining a brief literature review and then conducts qualitative research (in-depth interview and participant observation) to explore sensory experience and perception of blind people. The result finds from the five elements, walls and windows are the most influential elements for blind people. The existence of a wall has the potential to be a wayfinding of haptic system and has an echo effect. While the aperture opening element influences the illumination of light as well as indicators of outside space limits. The research outcome shows that people with visual impairment also acknowledge and they recognize these principles of design. They recognize contrast of temperature through the opening element, rhythm of texture through the wall, surface balance through the furniture, and hierarchy of noise through the window.